Ecologic and pastoral value of pastures of Sicilian mountains - Copani V.; Riggi E.; Cosentino S.L.; Testa G.; Virgillito S. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
In the park of Nebrodi Mountains (Sicily, Italy), from the autumn 2000 to the spring 2001 a floristic analysis and a productivity assessment in relation to agronomic treatments (N, P, N+P fertilisation and irrigation) were carried out in three pasture areas between 1148 and 815 m asl. The species with high fodder value were frequently reported in the most elevated site. The pastures of higher altitudes are included in the class of Cirsietalia Vallis demonis, a local variant of the Molinio-Arrhenatheretea class, which characterizes high altitude pastures. In warmer environments the pasture of secondary source prevails, class Lygeo-Stipetea and Poetea bulbosae (especially perennial) and Tuberarietea guttatae class (annual). Agronomic treatments differently increase yield regarding environment and vegetation. Best performances were obtained using phosphatic fertilisation and irrigation at lower altitudes, whereas at higher altitudes nitrogen fertilisation was the best treatment.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)